IMPROVING STUDENTS’ LISTENING SKILLS BY USING THE SPOTIFY APP - Fitri Novia; Kiki Rizki Amelia; Afriyani (Universitas Islam Ogan Komering Ilir Kayuagung, 2025)
A crucial component of learning a language is developing one's listening skills. However, students struggled with their listening skills. The issues included dialects, unclear pronunciation, a lack of vocabulary, and the audio's speed. Students' listening skills issues might be resolved with the help of the Spotify app. The study aimed to determine whether there was a significant difference in the listening skills of students who received instruction using the Spotify application compared to those who did not. This study was carried out using a quasi-experimental method. To examine the data, a t-test was employed. Based on the independent sample t-test results, it was revealed that pvalue (0.000) was less than ɑvalue (0.05) and the t-test achieved (5.362) was greater than the t-table (2.0345). It indicated that students who received instruction using the Spotify app and those who did not have significantly different listening skills. Thus, students can learn how to listen better by using the Spotify app as a teaching tool